(untitled) (Journal of Information Technologies in Education (ITE), 2009)
Conception of construction of the intellectual automated systems of evaluation of knowledge’s. The offered system foresees the presence of such subsystems: functional subsystem of transformation of information from external representation in intersystem information; subsystems of transformation from intersystem presentation of information in external information; subsystems of representation of knowledge’s, which includes the block of forming of results and system of artificial intelligence.